2019
DOI: 10.1007/s13595-018-0796-5
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding depression and differential maladaptation shape the fitness trajectory of two co-occurring Eucalyptus species

Abstract: & Key message The fitness trajectory of long-lived forest species with mixed mating systems is shaped by a dynamic interplay between endogenous (inbreeding depression) and exogenous (environmental maladaptation) factors. Using two eucalypt species, we show that the timing and translation of inbreeding depression from growth to survival through size-dependent mortality may vary between species and may intensify under climate stress. & Context Inbreeding is an important issue in evolutionary biology and breeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 75 publications
1
23
0
Order By: Relevance
“…Similarly, some populations of Eucalyptus globulus show high susceptibility to inbreeding depression, while purging of genetic load may reduce vulnerability to inbreeding depression in others including the relatively isolated King Island population of E. globulus that has low levels of heterozygosity (Costa e Silva et al, 2011;Steane et al, 2006). Thus, plant populations that vary in mating history may also display differences in the extent to which genetic variation impacts fitness (Keller & Waller, 2002;Nickolas, Harrison, Tilyard, Vaillancourt, & Potts, 2019).…”
Section: Low Levels Of Genetic Diversity Are Not Related To Populatmentioning
confidence: 99%
“…Similarly, some populations of Eucalyptus globulus show high susceptibility to inbreeding depression, while purging of genetic load may reduce vulnerability to inbreeding depression in others including the relatively isolated King Island population of E. globulus that has low levels of heterozygosity (Costa e Silva et al, 2011;Steane et al, 2006). Thus, plant populations that vary in mating history may also display differences in the extent to which genetic variation impacts fitness (Keller & Waller, 2002;Nickolas, Harrison, Tilyard, Vaillancourt, & Potts, 2019).…”
Section: Low Levels Of Genetic Diversity Are Not Related To Populatmentioning
confidence: 99%
“…The use of above-ground growth as a fitness surrogate has been suggested in long-lived species, such as forest trees, particularly at young stages when plants have not reached reproductive maturity [31,32]. Within eucalypt species, radial stem size (e.g., diameter or basal area) and tree height are usually highly positively correlated at the genetic and phenotypic levels [33] and for trees of the same cohort grown under competition, survival increases with radial stem size [34][35][36], consistent with size-dependent mortality [37]. Nevertheless, although HT growth 44 months after planting may be considered as a fitness surrogate in an early stage of a tree's life cycle, it will not necessarily represent a major component of lifetime fitness.…”
Section: Common-garden Experiments and Measurementsmentioning
confidence: 99%
“…Similar patterns are seen in other widespread tree species with large population sizes across various regions of the world, including other Eucalyptus species (Bloomfield et al., 2011; Jones et al., 2013; Murray et al., 2019; Nevill, Bradbury, et al., 2014; Supple et al., 2018), Quercus (Ju et al., 2019), Populus (Keller et al., 2010), and Pinus (Potter et al., 2015), which show limited genetic structuring; with isolation by distance explaining much of the genetic divergence. In the case of eucalypts, it has been suggested that their high recombination rates (Gion et al., 2016), preferential outcrossing (Byrne, 2008; Horsley & Johnson, 2007), and substantial inbreeding depression in the case of selfing (Nickolas et al., 2019), all favor the retention of genetic diversity and a lack of geographical structuring despite lacking long distance dispersal capabilities (Booth, 2017).…”
Section: Discussionmentioning
confidence: 99%